Effect of breed as a risk factor for humeral condylar fracture in skeletally immature dogs. (23rd April 2020) - Smith, M. A. J.; Jenkins, G.; Dean, B. L.; O'Neill, T. M.; Macdonald, N. J.
Abstract : Objectives: To investigate the effect of breed as a risk factor associated with humeral condylar fracture in skeletally immature dogs in the UK. Materials and Methods: Retrospective study of dogs under 12 months of age that were presented with humeral condylar fracture to three specialist referral centres between 2015 and 2018. Data retrieved from medical records included breed, age, gender, neuter status, affected limb, fracture configuration and aetiology of the fracture. Breed population percentages were compared with those recorded by the UK Kennel Club. Results: Of the 115 dogs with 118 fractures, French bulldogs (41%) and English springer spaniels (15%) were overrepresented: humeral condylar fractures were more commonly diagnosed in French bulldogs (odds ratio = 5.86) and English springer spaniels (odds ratio = 5.66) compared with mixed‐breed dogs. Lateral condylar fractures occurred in 70% of cases, with medial condylar fractures and Y/T fractures accounting for 9% and 21%, respectively. Median age at the time of fracture was 4 months (range 2 to 10 months). Clinical Significance: French bulldogs and English springer spaniels were identified as being at potentially increased risk of humeral condylar fracture in skeletally immature dogs.